Sensitivity of rainfed okra (Abelmoschus esculentus L. Moench) to mulch material and plant spacing in drought-prone tropical soils (Agroindustrial Science, 2024)
Mulch regulates soil hydrothermal regime while suppressing weed growth, effects of which may depend on mulch material and/or similar to that of closed crop canopy. Combined use of organic or inorganic material as surface mulch and appropriate plant spacing may produce synergistic agronomic effects in water-stressed environments. This study evaluated the sensitivity of rainfed okra to mulch-spacing variants in droughty derived-savannah soils. With dry-grass mulch (DGM) and sawdust mulch (SDM) representing organic mulch material and black polythene (BPM) as inorganic/plastic, treatments were factorial combinations of surface-applied DGM, SDM and BPM with close (60 cm × 30 cm), intermediate (60 cm × 45 cm) and wide (60 cm × 60 cm) spacings. Crop growth/performance and fruit yield data were collected. Mulch material affected okra growth (with overall better results in BPM than SDM), but not flowering/fruiting and fruit yield. For plant spacing, sum of weights of pods and fruit yield were higher in close than intermediate and wide spacings, with fruit yields as 2.42, 1.21 and 0.76 t ha-1, respectively. Mulch-spacing interaction effects showed that BPM with close spacing gave the highest values for stem girth 8 weeks after sowing (SDM treatments gave the lowest), sum of weights of pods and fruit yield (2.93 t ha-1). Fruit yield, however, depended not on stem girth but on certain okra yield attributes. The BPM or, where not feasible, either of DGM and SDM, could be effectively combined with close spacing to improve okra productivity in droughty soils of the derived savannah.
Keywords: water-stressed environments; surface mulching; black polythene mulch; close spacing; plant density; okra fruit yield.; water-stressed environments; surface mulching; black polythene mulch; close spacing; plant density; okra fruit yield